A comparative longitudinal study of non-verbal mouse pointer - Mahmud, Murni; Sporka, Adam J.; ., Sri Kurniawan; Slavik, Pavel (Springer-Verlag, 2007)
A longitudinal study of two non-speech continuous cursor control system is presented in this paper;Whistling User Interface (U3I)and Vocal Joystick (VJ). This study combines the quantitative and qualitative methods to get a better understanding of novice users' experience over time. Three hypotheses were tested in this study. The quantitative data show that U3I performed better in error rate and in stimulating a mouse click; VJ was perceived as less fatiguing than VJ. U3I approached the performance of VJ at the end of the study period, indicating that these two systems can achieve similar performances as users get more experienced in using them. This study supports two hypotheses but does not provide enough evidence to support one hypothesis.